"Triple Target" policy framework to influence household energy behavior: Satisfy, strengthen, include. (1st July 2020) - Spandagos, Constantine; Yarime, Masaru; Baark, Erik; Ng, Tze Ling
Highlights: Energy consumers' perceptions of "selfish" and "self-less" objectives are explored. Significant differences are observed depending on type of energy behavior targeted. The environment is evaluated higher in efficiency than in conservation. Perceptions are affected more by psycho-cognitive traits, less by socio-demographics. A holistic, inclusive policy framework for targeted behavioral change is proposed. Abstract: A broader understanding of the behavioral aspect of energy consumption is increasingly critical for the formulation of policies that are effective in encouraging households to save energy. Such understanding is currently hindered, as the two counterparts of energy-saving behavior, namely efficiency and conservation, are not examined holistically; it is also hindered by the limited exploration of the underlying factors that may shape energy consumers' perceptions of environmental, economic and comfort objectives. To address these research gaps, this paper is examining air-conditioning energy use patterns and attitudes in an urban setting, and provides evidence that consumer perceptions are affected by the choice of behavior: for instance, the importance scores assigned to environmental and economic objectives for efficiency behavior are by 33% higher compared to those for conservation behavior. On the other hand, comfort is the most important objective for conservation. Moreover, these perceptions are found to be affected more by the consumers' psycho-cognitive characteristics, and less by socio-demographics. These findings introduce the "Triple Target" framework, to aid policy-makers in stimulating targeted behavioral change by means of: satisfying the most important objectives for each behavior; strengthening population characteristics that positively affect change; including as many population segments as possible, without considering socio-demographics as barriers to energy-saving. In this direction, the development of smart technology can be utilized to better inform residents about all the possible benefits associated with the two behaviors. Finally, insulation developments and extended labeling programs can be utilized to further enhance such efforts for conservation and efficiency, respectively.